1995
DOI: 10.1002/j.1460-2075.1995.tb07139.x
|View full text |Cite
|
Sign up to set email alerts
|

The solution structure of the RING finger domain from the acute promyelocytic leukaemia proto-oncoprotein PML.

Abstract: Acute promyelocytic leukaemia (APL) has been ascribed to a chromosomal translocation event which results in a fusion protein comprising the PML protein and the retinoic acid receptor alpha. PML is normally a component of a nuclear multiprotein complex (termed ND10, Kr bodies, nuclear bodies, PML oncogenic domains or PODs) which is disrupted in the APL disease state. PML contains a number of characterized motifs including a Zn2+ binding domain called the RING or C3HC4 finger. Here we describe the solution struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
247
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(264 citation statements)
references
References 34 publications
16
247
0
1
Order By: Relevance
“…For PML, disruption of other regions of the protein, including the leucine coiled coil and B-box motifs, did not a ect its ability to bind PRH indicating that these domains were not required for interaction. Western and immuno¯uorescence analysis con®rmed that PML, Z and PRH mutants used were produced to levels similar to respective wild-type proteins (Borden et al, 1995(Borden et al, , 1998a; data not shown).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…For PML, disruption of other regions of the protein, including the leucine coiled coil and B-box motifs, did not a ect its ability to bind PRH indicating that these domains were not required for interaction. Western and immuno¯uorescence analysis con®rmed that PML, Z and PRH mutants used were produced to levels similar to respective wild-type proteins (Borden et al, 1995(Borden et al, , 1998a; data not shown).…”
Section: Resultsmentioning
confidence: 82%
“…Both colorometric and liquid culture assays were used to monitor results ( Figure 1a,b). For both PML and Z point mutations which caused misfolding of the RING domain (Borden et al, 1995(Borden et al, , 1998a, denoted PMLRING and ZRING, abrogated the ability of either protein to bind PRH. Other regions of PML were deleted to determine if they were necessary for the interaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, another report indicated that both PML and the translocation fusion product PMLRARa are capable of inducing the transcriptional activity of steroid hormone receptors, and altering their subcellular distribution (GuiochonMantel et al, 1995). Because, PML does not bind DNA, it is postulated that its e ects on transcription are through protein-protein interactions with other factors involved in transcription regulation (Borden et al, 1995). Supporting the above hypothesis, recent analysis of the solution structure of the PML RING®nger suggests that this region may be involved in protein-porotein interactions (Borden et al, 1996).…”
Section: Introductionmentioning
confidence: 99%